Geoneutrino oscillations approach to discriminate distributions of heat producing elements in the earth's mantle (2018)
Neutrinos are still an intriguing subject in physics due to their odd properties, nonetheless there is a rising field on Neutrino Geoscience that uses these properties to study the Earth. This project shows the results of the simulations done in order to calculate the expected geoneutrino signal (electron antineutrinos from natural beta decay) from different mantle distributions of Heat Producing Elements and Bulk Silicate Earth models. The probability of detecting a geoneutrino is called survival probability. The average two-flavor survival probabilities and an exact approach to matter-oscillations are used. Both results are very similar, given that the exact solution gives an average value of Pee = 0.56. These results are in agreement with previous estimations and with mantle flux measurements from KamLAND and Borexino, but the model used for the Earth causes discrepancies when calculating the total flux. The software developed was tested with solar neutrinos and gave satisfactory results, demonstrating the accuracy of its calculations. So far, geoneutrinos have proven to be an useful tool to understand the chemical composition of the planet. However, the resolution of the detectors is a significant limitation; improvements in this matter are expected in the years to come